PERENCANAAN REKRUTMEN TENAGA PENDIDIK DI TINGKAT SMA - Ridho Dwi Putra; Zainal Berlian; Baharudin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study is entitled "Educator Recruitment Planning at the High School Level". This study aims to analyze the planning of educator recruitment at the high school level and the supporting and inhibiting factors of educator recruitment planning at the high school level. In this study, the researcher used a qualitative descriptive approach using qualitative research types. In this study, the research informants were the Principal, the Vice Principal of Curriculum and the Head of Administration. Data collection techniques used were observation, interviews, and documentation. While the techniques used in data analysis were data reduction, data presentation, data verification, and conclusion drawing. The test of the validity of this research data used source triangulation and technical triangulation. The results of the study indicate that the planning of educator recruitment at the high school level has been running quite well. The results of this study can be seen in the formulation of the current situation in the preparation of new educator recruitment, the distribution of new educator recruitment announcements, the acceptance of new educator applications, and the selection of applicants, the determination in the preparation of new educator recruitment, the distribution of new educator recruitment announcements, the acceptance of new educator applications and the selection of applicants. Identifying all the obstacles and facilitations in preparing for new teacher recruitment, distributing announcements, accepting new teacher applications, and selecting applicants. The inhibiting factors include the uncertain timing of teacher recruitment and the difficulty of obtaining competent teachers.